The Role of Labor Market Rigidities During the Transition : Lessons From Poland - Pujol, Thierry (IMF Working Papers; Working Paper ;, 1996)
The transition to a market economy has been analyzed primarily from a stabilization prospective. To complement that approach, we focus on a pure relative price shock and subsequent price adjustments. A model of monopolistic competition with costly labor adjustment indicates that relative price shocks can induce overall output decline because rigid sectoral real wages do not adjust to offset sectoral price changes, and firms that benefit from the price shock engage in monopolistic behavior. In Poland, empirical evidence suggests that relative wage rigidity contributed to lower employment and output, but there is no strong evidence that competition was important.